REGULATORY FRAMEWORK FOR REGULATING ON ESG AUDITING (International Congress on Economics, Management and Business Studies, 2026)
In this thesisESG audit and regulatory framework for its regulation It provides an opportunity to deeply analyze the possibilities of application in the economic conditions of our country.
Keywords: General requirements for financial disclosures related to sustainability, Climate Disclosure Standard,Sustainability Reporting Standards, GRI standards